Proyecto asociativo de producción y comercialización de jarabe de sábila-jengibre y miel de abeja proveniente de la zona Gualea Cruz para la ciudad de Quito - Quinteros Miño, Carlos Gustavo (2015)
This associative project is done at the Gualea Cruz, is the production and marketing of aloe-ginger and honey´s syrup with a group of entrepreneurs who want to start a new business and generate jobs for people. This project aims to organize entrepreneurs through cooperation and mutual assistance and people from that place have a job besides they have the opportunity to improve their way of living. This research was made in 6 chapters: Chapter 1: Problem research and the analysis of the objectives to determinate what we´ll get with project implementation. Chapter 2: Theorical framework is the guide to support concepts used in the following chapters. Chapter 3: Methodological framework indicates method that will be done, techniques and data collection required. Chapter 4: The market study allows observing supply and demand in the market and let know if people will buy this new product or not. Chapter 5: Technical study shows the structure of the organization, machinery, materials and resources that enterprise needs to begin its activities. Chapter 6: Financial study shows the initial investment required for the project. Finally, the conclusions, proposals and recommendations for the project, which should be applied, controlled and evaluated